Characterization and Optimal Design of Silicon-Rich Nitride Nonlinear Waveguides for 2 μm Wavelength Band - Zhihua Tu; Daru Chen; Hao Hu; Shiming Gao; Xiaowei Guan (Applied Sciences, 2020)
Optical communication using the 2 μm wavelength band is attracting growing attention for the sake of mitigating the information ‘capacity crunch’ on the way, where on-chip nonlinear waveguides can play vital roles. Here, silicon-rich nitride (SRN) ridge waveguides with different widths and rib heights are fabricated and measured. Linear characterizations show a loss of ~2 dB/cm of the SRN ridge waveguides and four-wave mixing (FWM) experiments with a continuous wave (CW) pump reveal a nonlinear refractive index of ~1.13 × 10−18 m2/W of the SRN material around the wavelength 1950 nm. With the extracted parameters, dimensions of the SRN ridge waveguides are optimally designed for improved nonlinear performances for the 2 μm band, i.e., a maximal nonlinear figure of merit (i.e., the ratio of nonlinearity to loss) of 0.0804 W−1 or a super-broad FWM bandwidth of 518 nm. Our results and design method open up new possibilities for achieving high-performance on-chip nonlinear waveguides for long-wavelength optical communications.